2014
DOI: 10.1159/000371743
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention Study of Individual, apoE Genotype-Based Dietary and Physical-Activity Advice: Impact on Health Behavior

Abstract: Aim: To assess the behavioral effects of receiving personal genetic information, using apoE genotypes as a tool for promoting lifestyle changes. apoE was chosen because it has a significant impact on lipid metabolism and cholesterol absorption, both factors in cardiovascular disease. Methods: This study was a 1-year intervention study of healthy adults aged 20-67 years (n = 107). Their behavioral changes were measured by diet (e.g., fat quality, as well as consumption of vegetables, berries, fruits, and fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(103 citation statements)
references
References 29 publications
2
98
0
3
Order By: Relevance
“…It is interesting to note the differences in the duration of follow-up within these studies, as the effect of genotype-based personalised advice was observed at 12 months in studies conducted by Arkadianos et al (29) and Nielsen & El-Sohemy (32) , but not reported in those studies of shorter duration (30) . However, Hietaranta-Luoma et al reported positive changes early on in the intervention, but these was no longer evident at 12 months (31) . At present, the evidence for the benefit of genotype-based PN is not strong, and more studies are warranted before any clear conclusions can be deduced on personalised advice based on genotype and motivating behaviour change.…”
Section: Studies Investigating the Impact Of Genotype-based Personalimentioning
confidence: 98%
See 3 more Smart Citations
“…It is interesting to note the differences in the duration of follow-up within these studies, as the effect of genotype-based personalised advice was observed at 12 months in studies conducted by Arkadianos et al (29) and Nielsen & El-Sohemy (32) , but not reported in those studies of shorter duration (30) . However, Hietaranta-Luoma et al reported positive changes early on in the intervention, but these was no longer evident at 12 months (31) . At present, the evidence for the benefit of genotype-based PN is not strong, and more studies are warranted before any clear conclusions can be deduced on personalised advice based on genotype and motivating behaviour change.…”
Section: Studies Investigating the Impact Of Genotype-based Personalimentioning
confidence: 98%
“…At 12 months, those with the risk version of ACE gene had significantly lower intakes of sodium compared with the control group (P = 0·008) Hietaranta-Luoma et al (31) Healthy adults aged 20-67 years (n 107)…”
Section: Studies Investigating the Impact Of Genotype-based Personalimentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous papers, we have reported psychological [26] and behavioral [27] effects. In the current paper, we focus on the effect of the specific risk factors of CVD.…”
Section: Introductionmentioning
confidence: 96%